Electronic Medical Records: between Legal Certainty and Legal Benefit - Francisca Romana Harjiyatni; Majd Almanasra; Lucky Isti Gupitasari (Jurnal Hukum, 2026)
Medical Records system to improve the quality of health services. Health care facilities that do not implement E-Medical Records are subject to administrative sanctions. This study aims to analyze the implications of E-Medical Records on improving health services and examine the enforcement of sanctions against health care facilities. This study is a doctrinal study, with data obtained through a literature review. The results of the study were analyzed qualitatively. The research findings show that there are still many health care facilities that have not implemented E-Medical Records, resulting in their inability to improve the quality of health services. The mandatory implementation of E-Medical Records and the accompanying sanctions are not yet fully appropriate for all health care facilities throughout Indonesia. It is necessary to implement sustainable actions to improve the quality of health services.